Polityka gospodarcza III Rzeszy w ujęciu polskich ekonomistów tamtego czasu - Kurowski, Lech; Szymaniec, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of this paper is to present Polish pre-war literature on Nazi economic policy and to compare Leopold Caro’s views with analyses of a well-known postwar economist, Paweł Sulmicki, presented in his doctoral thesis of 1946. The comparison of these two interpretations enables the authors to show not only the change of views on the totalitarian economy of Germany, but also the transformations that took place in the Polish theory of economics at that time. In terms of methodology, the work of Leopold Caro (published in 1938) did not go beyond what the German historical school offered. Paweł Sulmicki, on the other hand, explained the processes taking place in the German economy from the point of view of the theory of multiplier which was relatively new at that time. Sulmicki did not explicitly state that the phenomena analyzed by him were paradoxes in the light of Keynesian theory, but he described the factors that led to the success of the economic policy at a low level of the multiplier.
Keywords: nazizm; polityka gospodarcza; mnożnik inwestycji; Sulmicki, Paweł; Caro, Leopold (1864-1939)